Estudo das interações enzima-suporte envolvidas na inativação de lipases imobilizadas em suportes octil-vinilsulfona - Souza, Priscila Maria Paiva (2022)
In this study, lipases from Thermomyces lanuginosus (TLL) and lipase B from Candida antarctica (CALB) were covalently immobilized on the heterofunctional support octyl-agarose activated with divinyl sulfone. The biocatalysts were blocked using hexylamine (HA), ethylenediamine (EDA), glycine (GLI), and aspartic acid (ASP) and had their activity, stability, specificity and structural interactions analyzed. Both enzymes showed differences in the stability after inactivation in 50 mM sodium acetate buffer pH 5 and 70 °C (TLL) and 80 °C (CALB), 50 mM sodium phosphate buffer pH 7 and 70 °C (TLL) and 75 °C (CALB) and 50 mM sodium carbonate buffer pH 9 and 65 °C (TLL) and 60 °C (CALB), in addition to showing variations in specificity using substrates with distinct structures such as pNPB, triacetin and (R)- and (S)-methyl mandelate. For the TLL biocatalysts, blocking with glycine showed the highest stability under all pH conditions. Analyzing the activity of TLL biocatalysts against different substrates, triacetin was the substrate that showed the fastest loss activity among all the blocked agents and pH tested. For CALB biocatalysts, the one blocked with glycine was the most stable at pH 5 and 7, while at pH 9, the stabilities differences between the blocked biocatalysts were reduced, and blocking with EDA followed by glycine was the most stable. Considering the substrate specificity of CALB biocatalysts, pNPB was the substrate that maintained the highest activities in all blocked preparations and inactivation percentages. It can be concluded that such differences were modulated by the immobilization protocol with different blocks and by the inactivation conditions and were confirmed by fluorescence studies. Among the TLL biocatalysts, fluorescence showed that, during the inactivation course, the structural distortions of HA-blocked TLL were more drastic (low Imax and redshifted λmax values) than with the other biocatalysts. For the CALB biocatalysts, the fluorescence spectrum analysis again revealed structural changes in the blocking with HA, which may explain the lower activity of this biocatalyst using pNPB. The functional and structural analysis of the immobilized and partially inactivated enzymes showed that the inactivation pathway depends on the support characteristics and inactivation conditions.